Analysis of role of rat cerebral pericytes in cerebral vasospasm after subarachnoid hemorrhage and molecular mechanism of neurovascular injury. Issue 1 (1st January 2021) - Yan, Zhenxing; Zou, Yang; Deng, Yiting; Liu, Siqin; Li, Kaifeng; Yang, Juan; Guo, Xihua; He, Rongni; Zheng, Wenxia; Xie, Huifang
ABSTRACT: To investigate mechanism of pericytes in the early stage of subarachnoid haemorrhage (SAH) and its associated microvascular spasm and neurovascular injury, 100 healthy 8-week-old Sprague-Dawley male rats were taken as subjects and divided into four groups: group A (sham operation, control group), group B (SAH operation group), group C (SAH operation group treated with scutellarin), and group D (SAH operation group treated with L-nitro-arginine). 72 hours after the operation, the rats were conducted assessment of neurological impairment, observation of microangiography, detection of blood-brain barrier permeability, observation of skull base haemorrhage, identification of pericyte culture, and measurement of blood nitric oxide. The results showed that neurological impairment score, degree of micro-vasoconstriction, and BBB permeability of group C were significantly better than those of group B and D (P<0.05), there was no significant difference between group C and group A (P>0.05). There were significantly fewer blood clots in the brain of group C, and the order of expression levels of α-smooth muscle actin (α-SMA) in perioperative cells of the four groups from highest to lowest were D, B, C, and A. Nitric oxide concentration inhibited expression of α-SMA in pericytes after SAH at both protein and mRNA levels. The detection results of nitric oxide in the blood of four groups of rats confirmed that pericyte phenotype conversion and actin α-SMA expression could be prevented by upregulation of nitric oxide in serum, so as to relieve pathological symptoms after SAH operation. Graphical abstract: uf0001